Earnings Management and the Market Performance of Stock Dividend Distributing Firms - kayhan maham; saeed alipour; bahman talebi (پژوهش‌های تجربی حسابداری, 2015)
This study evaluates the relation between earnings management and the market performance of dividend distributing firms listed in Tehran Stock Exchange. To test earning management, the modified accrual model of Jones has been used. The sample consists of 87 firms in the period from the years 2005 to 2011. The findings show that Stock dividend distributing firms report higher accruals in the event year than those in the pre-event year.  Also, findings show that future earnings and stock returns of these firms have negative relation with accruals.